산림작물 생산기반조성 재정성과 모니터링 - 석현덕 (한국농촌경제연구원, 2008)
The purpose of this study is to drive a sustainable forest management by way of monitoring forest crop production system establishment projects which is conducted by the Korean Forest Service. The monitoring process is consist of three phases ; policy performance ability, project performance spot inspection, and survey of policy recipients. Though several problems in project are revealed, the monitoring results show that the project generally performs well. Most of the revealed problems are being fixed by way of feedbacking process. Policy implications and future proposals for enhancing the performance of projects are also proposed. Researchers: Hyun Deok Seok(Ph.D.), Seong Ju Kim E-mail address: hdseok@krei.re.kr